The Blackfeet : people of the dark moccasins - Gibson, Karen Bush (Mankato, Minn. : Bridgestone Books, 2003)
An overview of the past and present of the Blackfeet people. Traces their customs, family life, history, and culture, as well as relations with the U.S. government.
Who are the Blackfeet? -- Traditional life -- U.S. expansion brings change -- The Blackfeet today -- Sharing the traditions.
Includes bibliographical references and index.
8 years and up
Keywords: Siksika Indians; Piegan Indians; Kainah Indians; Indians of North America -- Great Plains